Functional adhesive for grinding and polishing disc brush and preparation method thereof

By introducing modified wear-resistant additives and functional components into the adhesive for polishing disc brushes, the oxidation and performance degradation of polyurethane adhesives under high temperature and high friction conditions is solved, and higher oxidation and wear resistance are achieved, extending service life and improving adhesion and mechanical strength.

CN119912896APending Publication Date: 2025-05-02GUANGZHOU DEHUI CHEM TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510027273.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

During the use of polyurethane adhesives in polishing disc brushes, high-speed friction causes temperature to rise, and oxidation may occur, resulting in reduced performance and failure of fallout. At the same time, their anti-oxidation and wear resistance are insufficient, which limits its application.

Method used

A functional adhesive is used, which includes 50-70 parts of polypolyol, 35-45 parts of diisocyanate, 0.3-0.6 parts of organotin catalyst, 10-15 parts of chain extender, 1-3 parts of defoaming agent, 3-5 parts of wear-resistant additives and 4-6 parts of functional components. The wear-resistant additives are combined with maifanite powder through modified wollastonite fibers, and the functional components are introduced into the hindered phenol structure through chemical bonding, improving antioxidant and bonding properties.

Benefits of technology

It improves the antioxidant and wear resistance of the adhesive, avoids oxidation, extends service life, and maintains excellent adhesion and mechanical strength under friction conditions, meeting the application needs of polishing and polishing disc brushes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912896A_ABST
    Figure CN119912896A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of adhesives, and discloses a functional adhesive for a grinding and polishing disc brush and a preparation method of the functional adhesive, the functional adhesive comprises the following raw materials: polyol, diisocyanate, an organic tin catalyst, a chain extender, a defoaming agent, a wear-resistant additive and a functional component, by preparing the wear-resistant additive, the mechanical property of the adhesive is effectively enhanced, the friction resistance is reduced, and the wear resistance of the adhesive is effectively enhanced, so that the application requirements of the grinding and polishing disc brush are met; the adhesive property, the oxidation resistance and the flexibility of the adhesive are effectively enhanced by preparing the functional components, the adhesive can be ensured to keep stable performance in the using process, the oxidation phenomenon is not prone to occurring, the adhesive can be firmly combined with an adhered base material, and the situation that the adhesive falls off or loses efficacy is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesives, and in particular to a functional adhesive for a grinding and polishing disc brush and a preparation method thereof. Background Art

[0002] Grinding and polishing disc brushes are one of the tools widely used in industry. They are mainly used for grinding, finishing, polishing, and deburring the surface of workpieces to improve the smoothness and precision of the workpiece surface. They are used in metal processing, wood processing, cleaning equipment, and cutting and grinding of materials such as ceramic tiles and floor tiles. In the use of grinding and polishing disc brushes, adhesives play a very important role. They can bond abrasives to ensure that the abrasives will not fall off during the grinding and polishing process, which is related to the quality and effect of grinding and polishing. Polyurethane adhesives have excellent low-temperature resistance, and also have certain resistance to solvents, oils, acids and alkalis. The bonding process is simple, the operability is good, and it can be cured at room temperature. It can improve to a certain extent. High work efficiency, so polyurethane adhesive can be selected as the adhesive for grinding and polishing disc brushes, but polyurethane adhesive also has its shortcomings. During the use of the grinding and polishing disc brush, high-speed friction movement will occur between the abrasive particles on the surface and the workpiece, resulting in the conversion of mechanical energy into thermal energy, causing the temperature to rise. The polyurethane adhesive may oxidize, resulting in the degradation of the adhesive performance and the phenomenon of shedding and failure, shortening the service life of the adhesive. In addition, since the grinding and polishing disc brush is constantly in contact and friction with the abrasive and the workpiece during use, the adhesive needs to have excellent wear resistance and can maintain excellent adhesion while bearing the friction, so modification of the polyurethane adhesive is very necessary.

[0003] The patent with publication number CN111349417B discloses a polyurethane adhesive composition and a polyurethane adhesive. The polyurethane adhesive is prepared from component A and component B. Component A includes 20-70wt.% of one or more bio-oil modified polyols; component B includes 50-90wt.% of one or more polyurethane prepolymers, and the polyurethane prepolymer is a terminal isocyanate product obtained by the reaction of an isocyanate monomer compound and a polyol compound. The prepared polyurethane adhesive has sufficient mechanical strength and bonding stability, but insufficient antioxidant and wear resistance, which limits the application of the polyurethane adhesive as an adhesive for grinding and polishing disc brushes. Therefore, the present invention provides a functional adhesive with excellent antioxidant and wear resistance, which can be used as an adhesive for grinding and polishing disc brushes and can meet the needs of different grinding application scenarios. Summary of the invention

[0004] In order to solve the technical problems mentioned in the background technology, the purpose of the present invention is to provide a functional adhesive for grinding and polishing disc brushes and a preparation method thereof.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] A functional adhesive for a grinding and polishing disc brush comprises the following raw materials in parts by weight: 50-70 parts of polyol, 35-45 parts of diisocyanate, 0.3-0.6 parts of organic tin catalyst, 10-15 parts of chain extender, 1-3 parts of defoamer, 3-5 parts of wear-resistant additive and 4-6 parts of functional components.

[0007] Furthermore, the polyol is polycarbonate diol or polytetramethylene glycol; the diisocyanate is any one of isophorone diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate or meta-xylyl isocyanate; the organotin catalyst is dibutyltin dilaurate or stannous octoate; the chain extender is any one of 1,4-butanediol, 1,3-propylene glycol or ethylene glycol; the defoamer is dimethyl silicone oil or polyoxypropylene glycerol ether.

[0008] Furthermore, the preparation method of the wear-resistant additive comprises the following steps:

[0009] Step S1: adding wollastonite fiber to deionized water, ultrasonically dispersing to form a uniform suspension, adding betaine hydrochloride and catalyst A, mixing evenly, raising the temperature to 100° C., reflux stirring for 1-3 hours, ending the reaction, cooling to room temperature, filtering, washing, and drying to obtain modified wollastonite fiber;

[0010] Step S2: Add the modified wollastonite fiber into deionized water, perform ultrasonic dispersion to form a uniform suspension, add medical stone powder, perform ultrasonic dispersion for 1-2 hours, let stand for 1-3 hours, collect the product, and obtain the wear-resistant additive.

[0011] By adopting the above technical scheme, the surface of the wollastonite fiber contains active hydroxyl groups, which can undergo esterification reaction with the carboxyl groups in the structure of betaine hydrochloride under the action of catalyst A, thereby introducing quaternary ammonium cations on the surface of the wollastonite fiber, making the wollastonite fiber positively charged, and producing electrostatic adsorption with the negatively charged medical stone powder, thereby realizing the combination of the wollastonite fiber and the medical stone powder to obtain a wear-resistant additive.

[0012] Furthermore, in step S1, the catalyst A is p-toluenesulfonic acid or aminosulfonic acid.

[0013] Furthermore, the preparation method of the functional component comprises the following steps:

[0014] Step A: adding polycaprolactone diol to N,N-dimethylformamide, stirring evenly, introducing nitrogen, adding 3-chloropropylamine hydrochloride and an alkaline catalyst, raising the temperature to 60-70°C, reacting for 3-5 hours, collecting the product, washing it, adding the product to deionized water, adding sodium hydroxide solution to adjust the pH, stirring for 20-40 minutes, discharging the material, and obtaining an intermediate product;

[0015] Step B: Add the intermediate product to dimethyl sulfoxide, stir evenly, then add 3,5-di-tert-butyl-4-hydroxybenzaldehyde and catalyst B, raise the temperature to 45-55° C., react for 3-4 hours, cool and discharge the material to obtain a functional component.

[0016] By adopting the above technical scheme, the hydroxyl group in the polycaprolactone diol structure can undergo a substitution reaction with the chlorine substituent in the 3-chloropropylamine hydrochloride structure under the action of an alkaline catalyst, and then an intermediate product with an amino group is obtained under the action of sodium hydroxide. Under the action of catalyst B, the amino group in the intermediate product structure can undergo a Schiff base reaction with the aldehyde group in the 3,5-di-tert-butyl-4-hydroxybenzaldehyde structure to obtain a functional component.

[0017] Furthermore, in step A, the alkaline catalyst is triethylamine.

[0018] Furthermore, in step A, the pH is 9.5-10.5.

[0019] Furthermore, in step B, the catalyst B is a sodium carbonate solution.

[0020] A method for preparing a functional adhesive for a grinding and polishing disc brush comprises the following steps:

[0021] Step 1: Add the polyol and functional components into a reaction kettle, vacuum dehydrate at a temperature of 100-120°C for 1-3h, then cool to 70-90°C, introduce nitrogen protection, add diisocyanate, stir for 1-2h, then add chain extender, continue stirring and react for 0.5-2h to obtain an intermediate;

[0022] Step 2: Add organic tin catalyst and wear-resistant additive to the intermediate, stir for 2-4 hours under vacuum conditions, cool to room temperature, add defoamer to the system, stir for 30-50 minutes, and then discharge the material to obtain a functional adhesive.

[0023] Beneficial effects of the present invention:

[0024] (1) The wear-resistant additive prepared by the present invention is organically modified to combine wollastonite fiber and medical stone powder, which can improve the compatibility problem between the wear-resistant additive and the adhesive, so that it can be evenly dispersed in the adhesive to avoid agglomeration problems, and can effectively improve the mechanical strength of the adhesive film after curing. At the same time, the wear-resistant additive can form a ball effect in the adhesive, converting sliding friction into rolling friction, reducing the friction coefficient, and also has a lubricating effect, reducing friction resistance, thereby improving the wear resistance of the adhesive and meeting the application requirements of grinding and polishing disc brushes.

[0025] (2) The functional component prepared by the present invention introduces a hindered phenol structure by chemical bonding, which can improve the antioxidant property of the adhesive and prevent the grinding and polishing disc brush from being oxidized due to excessive temperature during use, which may cause the adhesive to fall off or fail. At the same time, it can also reduce the probability of precipitation of antioxidants and ensure the long-term antioxidant property of the adhesive. The ether bond contained in the functional component can improve the bonding property of the adhesive and ensure a strong bond with the bonded substrate. The polycaprolactone diol in the functional component can absorb and disperse the impact energy when the adhesive is subjected to external force, thereby improving the flexibility of the adhesive. The hydroxyl group contained in the functional component can interact with the isocyanate group in the preparation process of the polyurethane adhesive, thereby generating cross-links with the adhesive molecular chain, further improving the bonding property and flexibility of the adhesive.

[0026] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0028] Figure 1 This is the infrared spectrum of the functional component prepared in the present invention. DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] The preparation methods of the wear-resistant additives and functional components in the following examples and comparative examples are as follows:

[0031] 1. Preparation of wear-resistant additives

[0032] Step S1: 3.6 g of wollastonite fiber is added into deionized water, ultrasonically dispersed to form a uniform suspension, 2 g of betaine hydrochloride and 0.5 g of p-toluenesulfonic acid are added, mixed evenly, the temperature is raised to 100° C., refluxed and stirred for 2 h, the reaction is terminated, cooled to room temperature, filtered, washed, and dried to obtain modified wollastonite fiber;

[0033] Step S2: Add 3.2 g of modified wollastonite fiber into deionized water, disperse by ultrasonic method to form a uniform suspension, add 3 g of medical stone powder, disperse by ultrasonic method for 2 h, let stand for 3 h, collect the product, and obtain a wear-resistant additive.

[0034] The elemental analysis of wollastonite fiber and modified wollastonite fiber was carried out using Var io EL Cube fully automatic elemental analyzer. The results showed that wollastonite fiber did not contain nitrogen, and the percentage of nitrogen in modified wollastonite fiber was 3.86%. It can be seen that betaine hydrochloride reacted with wollastonite fiber, introducing quaternary ammonium cations to provide a nitrogen source.

[0035] 2. Preparation of functional components

[0036] Step A: Add 4 g of polycaprolactone diol to N,N-dimethylformamide, stir evenly, introduce nitrogen, add 2.3 g of 3-chloropropylamine hydrochloride and 0.6 g of triethylamine, raise the temperature to 65°C, react for 4 hours, collect the product, wash it, add the product to deionized water, add sodium hydroxide solution to adjust the pH to 10, stir for 30 minutes, discharge the material, and obtain an intermediate product;

[0037] Step B: Add 3.5 g of the intermediate product to dimethyl sulfoxide, stir evenly, then add 2 g of 3,5-di-tert-butyl-4-hydroxybenzaldehyde and 0.4 mL of 1 g / mL sodium carbonate solution, raise the temperature to 50°C, react for 3 hours, cool and discharge the material to obtain a functional component.

[0038] The functional components were tested by infrared spectrometer using Bruker TENSORⅡ. Figure 1 As shown, analysis shows that 3300cm -1 The absorption peak of phenolic hydroxyl group OH appeared at 3034 cm -1 The absorption peak of CH in the benzene ring appeared at 1731 cm -1 The absorption peak of C=O in the ester group appeared at 1622 cm -1 The absorption peak of Schiff base C=N appears at 1100 cm -1 The absorption peak of ether bond COC appeared.

[0039] Example 1

[0040] Preparation of functional adhesives

[0041] Step 1: Add 50g of polycarbonate diol and 4g of functional components into a reactor, vacuum dehydrate at 100°C for 1h, then cool to 70°C, introduce nitrogen protection, add 35g of diphenylmethane diisocyanate, stir for 1h, then add 10g of 1,3-propylene glycol chain extender, continue stirring and react for 0.5h to obtain an intermediate;

[0042] Step 2: Add 0.3g of dibutyltin dilaurate and 3g of wear-resistant additives to the intermediate, stir for 2h under vacuum conditions, cool to room temperature, add 1g of polyoxypropylene glycerol ether defoamer to the system, stir for 30min, and then discharge the material to obtain a functional adhesive.

[0043] Example 2

[0044] Preparation of functional adhesives

[0045] Step 1: Add 60g of polycarbonate diol and 5g of functional components into a reactor, vacuum dehydrate at 110°C for 2h, then cool to 80°C, introduce nitrogen protection, add 40g of diphenylmethane diisocyanate, stir for 1.5h, then add 12g of 1,3-propylene glycol chain extender, continue stirring and react for 1h to obtain an intermediate;

[0046] Step 2: Add 0.4 g of dibutyltin dilaurate and 4 g of wear-resistant additives to the intermediate, stir for 3 hours under vacuum conditions, cool to room temperature, add 2 g of polyoxypropylene glycerol ether defoamer to the system, stir for 40 minutes, and then discharge the material to obtain a functional adhesive.

[0047] Example 3

[0048] Preparation of functional adhesives

[0049] Step 1: Add 70g of polycarbonate diol and 6g of functional components into a reactor, vacuum dehydrate at 120°C for 3h, then cool to 90°C, introduce nitrogen protection, add 45g of diphenylmethane diisocyanate, stir for 2h, then add 15g of 1,3-propylene glycol chain extender, continue stirring and react for 2h to obtain an intermediate;

[0050] Step 2: Add 0.6g of dibutyltin dilaurate and 5g of wear-resistant additives to the intermediate, stir for 4h under vacuum conditions, cool to room temperature, add 3g of polyoxypropylene glycerol ether defoamer to the system, stir for 50min, and then discharge the material to obtain a functional adhesive.

[0051] Comparative Example 1

[0052] Preparation of functional adhesives

[0053] Step 1: Add 60g of polycarbonate diol and 5g of functional components into a reactor, vacuum dehydrate at 110°C for 2h, then cool to 80°C, introduce nitrogen protection, add 40g of diphenylmethane diisocyanate, stir for 1.5h, then add 12g of 1,3-propylene glycol chain extender, continue stirring and react for 1h to obtain an intermediate;

[0054] Step 2: Add 0.4 g of dibutyltin dilaurate to the intermediate, stir for 3 hours under vacuum conditions, cool to room temperature, add 2 g of polyoxypropylene glycerol ether defoamer to the system, stir for 40 minutes, and then discharge the material to obtain a functional adhesive.

[0055] Comparative Example 2

[0056] Preparation of functional adhesives

[0057] Step 1: Add 60g of polycarbonate diol into a reactor, vacuum dehydrate at 110°C for 2h, then cool to 80°C, introduce nitrogen protection, add 40g of diphenylmethane diisocyanate, stir for 1.5h, then add 12g of 1,3-propylene glycol chain extender, continue stirring and react for 1h to obtain an intermediate;

[0058] Step 2: Add 0.4 g of dibutyltin dilaurate and 4 g of wear-resistant additives to the intermediate, stir for 3 hours under vacuum conditions, cool to room temperature, add 2 g of polyoxypropylene glycerol ether defoamer to the system, stir for 40 minutes, and then discharge the material to obtain a functional adhesive.

[0059] Comparative Example 3

[0060] Preparation of functional adhesives

[0061] Step 1: Add 60g of polycarbonate diol and 5g of polycaprolactone diol into a reaction kettle, vacuum dehydrate at 110°C for 2h, then cool to 80°C, introduce nitrogen protection, add 40g of diphenylmethane diisocyanate, stir for 1.5h, then add 12g of 1,3-propylene glycol chain extender, continue stirring and react for 1h to obtain an intermediate;

[0062] Step 2: Add 0.4 g of dibutyltin dilaurate and 4 g of wear-resistant additives to the intermediate, stir for 3 hours under vacuum conditions, cool to room temperature, add 2 g of polyoxypropylene glycerol ether defoamer to the system, stir for 40 minutes, and then discharge the material to obtain a functional adhesive.

[0063] Comparative Example 4

[0064] Preparation of functional adhesives

[0065] Step 1: Add 60g of polycarbonate diol and 5g of functional components into a reactor, vacuum dehydrate at 110°C for 2h, then cool to 80°C, introduce nitrogen protection, add 40g of diphenylmethane diisocyanate, stir for 1.5h, then add 12g of 1,3-propylene glycol chain extender, continue stirring and react for 1h to obtain an intermediate;

[0066] Step 2: Add 0.4 g of dibutyltin dilaurate, 2 g of wollastonite fiber and 2 g of medical stone powder to the intermediate, stir for 3 hours under vacuum conditions, cool to room temperature, add 2 g of polyoxypropylene glycerol ether defoamer to the system, stir for 40 minutes, and then discharge the material to obtain a functional adhesive.

[0067] Performance Testing

[0068] The functional adhesives prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were uniformly coated on a glass plate, and after being completely cured, adhesive films were obtained, which were prepared into samples that met the test specifications and subjected to the following tests: a 180° peel strength test was conducted in accordance with GB / T2792-2014 standard to determine the bonding performance of the sample; the sample was placed in an aging box at 100°C for 72 hours, and then a 180° peel strength test was conducted again to determine the antioxidant performance of the sample; the elongation at break of the sample was tested in accordance with GB / T1040.3-2006 standard to determine the flexibility of the sample; the tensile strength of the sample was tested in accordance with GB / T 1040.3-2006 standard to determine the mechanical properties of the sample; the wear resistance was tested by the following method: the sample was placed on a grinding rotary test bench, the sample was rubbed at a speed of 60 r / min, the load was set to 1000 g, and the wear amount of the sample was tested after rotating 5000 revolutions to determine the wear resistance of the sample. The test results are shown in the following table:

[0069]

[0070] As can be seen from the above table, the functional adhesives prepared by Examples 1 to 3 of the present invention have excellent viscosity, antioxidant properties, flexibility and wear resistance, and excellent mechanical properties. Comparative Example 1 adds a functional component without adding a wear-resistant additive, so the bonding performance, antioxidant performance and flexibility are excellent, but the mechanical properties and wear resistance are poor; Comparative Example 2 adds a wear-resistant additive without adding a functional component, and the wear resistance and mechanical properties are excellent, but the bonding performance, antioxidant performance and flexibility are poor; Comparative Example 3 adds polycaprolactone diol and wear-resistant additives, has good flexibility, decreased bonding performance, poor antioxidant performance, and excellent wear resistance and mechanical properties; Comparative Example 4 adds wollastonite fiber, medical stone powder and functional components, and the wollastonite fiber and medical stone powder are slightly agglomerated without modification, and a ball effect cannot be formed, resulting in decreased mechanical properties and wear resistance, and excellent bonding performance, antioxidant performance and flexibility.

[0071] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A functional adhesive for a grinding and polishing disc brush, characterized in that: The invention comprises the following raw materials in parts by weight: 50-70 parts of polyol, 35-45 parts of diisocyanate, 0.3-0.6 parts of organic tin catalyst, 10-15 parts of chain extender, 1-3 parts of defoamer, 3-5 parts of wear-resistant additive and 4-6 parts of functional component.

2. The functional adhesive for grinding and polishing disc brush according to claim 1, characterized in that: The polyol is polycarbonate diol or polytetramethylene glycol; the diisocyanate is any one of isophorone diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate or meta-xylylene diisocyanate; the organic tin catalyst is dibutyltin dilaurate or stannous octoate; the chain extender is any one of 1,4-butanediol, 1,3-propylene glycol or ethylene glycol; and the defoamer is dimethyl silicone oil or polyoxypropylene glycerol ether.

3. The functional adhesive for grinding and polishing disc brush according to claim 1, characterized in that: The preparation method of the wear-resistant additive comprises the following steps: Step S1: adding wollastonite fiber to deionized water, ultrasonically dispersing to form a uniform suspension, adding betaine hydrochloride and catalyst A, mixing evenly, raising the temperature to 100° C., reflux stirring for 1-3 hours, ending the reaction, cooling to room temperature, filtering, washing, and drying to obtain modified wollastonite fiber; Step S2: Add the modified wollastonite fiber into deionized water, perform ultrasonic dispersion to form a uniform suspension, add medical stone powder, perform ultrasonic dispersion for 1-2 hours, let stand for 1-3 hours, collect the product, and obtain the wear-resistant additive.

4. The functional adhesive for grinding and polishing disc brushes according to claim 3, characterized in that: In step S1, the catalyst A is p-toluenesulfonic acid or aminosulfonic acid.

5. The functional adhesive for grinding and polishing disc brush according to claim 1, characterized in that: The preparation method of the functional component comprises the following steps: Step A: adding polycaprolactone diol to N,N-dimethylformamide, stirring evenly, introducing nitrogen, adding 3-chloropropylamine hydrochloride and an alkaline catalyst, raising the temperature to 60-70°C, reacting for 3-5 hours, collecting the product, washing it, adding the product to deionized water, adding sodium hydroxide solution to adjust the pH, stirring for 20-40 minutes, discharging the material, and obtaining an intermediate product; Step B: Add the intermediate product to dimethyl sulfoxide, stir evenly, then add 3,5-di-tert-butyl-4-hydroxybenzaldehyde and catalyst B, raise the temperature to 45-55° C., react for 3-4 hours, cool and discharge the material to obtain a functional component.

6. The functional adhesive for grinding and polishing disc brushes according to claim 5, characterized in that: In step A, the alkaline catalyst is triethylamine.

7. The functional adhesive for grinding and polishing disc brushes according to claim 5, characterized in that: In step A, the pH is 9.5-10.

5.

8. The functional adhesive for grinding and polishing disc brushes according to claim 5, characterized in that: In step B, the catalyst B is a sodium carbonate solution.

9. A method for preparing a functional adhesive for a grinding and polishing disc brush according to claim 1, characterized in that: The following steps are involved: Step 1: Add the polyol and functional components into a reaction kettle, vacuum dehydrate at a temperature of 100-120°C for 1-3h, then cool to 70-90°C, introduce nitrogen protection, add diisocyanate, stir for 1-2h, then add chain extender, continue stirring and react for 0.5-2h to obtain an intermediate; Step 2: Add organic tin catalyst and wear-resistant additive to the intermediate, stir for 2-4 hours under vacuum conditions, cool to room temperature, add defoamer to the system, stir for 30-50 minutes, and then discharge the material to obtain a functional adhesive.

Citation Information

Patent Citations

  • A polyurethane adhesive composition and a polyurethane adhesive

    CN111349417B